2014
DOI: 10.1590/abd1806-4841.20142400
|View full text |Cite
|
Sign up to set email alerts
|

Utility of dermoscopy for demarcation of surgical margins in Mohs micrographic surgery

Abstract: BACKGROUNDSkin cancer is the most common malignancy and can be treated in various ways. One treatment modality is Mohs micrographic surgery. Due to the increasing incidence of skin cancer in the last decades, there is a need for improvement of the Mohs technique to optimize its effectiveness. OBJECTIVEThe aim of this study was to evaluate the use of dermoscopy to guide demarcation of Mohs micrographic surgery margins and ascertain whether this method can reduce operative time and, therefore, reduce surgical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 18 publications
1
32
0
2
Order By: Relevance
“…Our study has shown that the use of noncontact dermoscopy to identify tumour margins prior to the debulking excision does not reduce the number of stages required in MMS, irrespective of clinician experience, clinical subtype and tumour histological growth pattern. Our findings are similar to those of others . Histological types under those we called ‘other’ included adnexal BCC, bowenoid actinic keratosis and a basisquamous variant of BCC.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our study has shown that the use of noncontact dermoscopy to identify tumour margins prior to the debulking excision does not reduce the number of stages required in MMS, irrespective of clinician experience, clinical subtype and tumour histological growth pattern. Our findings are similar to those of others . Histological types under those we called ‘other’ included adnexal BCC, bowenoid actinic keratosis and a basisquamous variant of BCC.…”
supporting
confidence: 91%
“…Our findings are similar to those of others. 3 Histological types under those we called Dermoscopy examination of BCC may identify a range of changes depending on the histological and clinical subtype. Our study failed to show any benefit of dermoscopy across all clinical types.…”
mentioning
confidence: 99%
“…Риск возникновения новых опухолей в пересчете на 100 тыс. населения среди мужчин со-ставляет 56 новых случаев, среди женщин -61 [18]. Есть основание полагать, что в нашей стране актив-ная и пассивная (при раннем обращении больного к врачу) выявляемость заболевших врачами-офталь-мологами находится еще на весьма невысоком уров-не (рис.…”
Section: результаты и обсужденияunclassified
“…А между тем риск возникновения новых опухолей в пересчете на 100 тыс. населения среди мужчин со-ставляет 56 новых случаев, среди женщин -61 [17]. Есть основания полагать, что в нашей стране ранняя [6,12].…”
Section: результаты и обсуждениеunclassified